Pengaruh Kualitas Data dan Sistem Pengendalian Intern Pemerintah terhadap Kualitas Informasi Akuntansi dengan Kualitas Sistem Keuangan Desa sebagai Variabel Intervening pada Nagari di Kabupaten Tanah Datar - Yulia, Rini (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
Application of Village Financial System (SISKEUDES) is an application developed by Badan Pengawasan dan Pembangunan (BPKP) in order to improve the quality of village finance governance.. This study aims to determine the influence of data quality, internal control system of the government against the quality of accounting information with the quality of village financial system as intervening variables in nagari in Tanah Datar regency. The data used in this study is the primary data in the form of questionnaires distributed on the object of research. This research is done through descriptive method of Ferivikatif. The number of questionnaires distributed is 75, but the questionnaire can be processed 50 sheets. Data analysis was done by using PLS analysis version 3.0. The results of this study proves that the quality of data does not affect the quality of accounting information and quality of village financial system. While the village financial system affects the quality of accounting information. The government's internal control system does not affect the quality of accounting information while the internal control system affects the quality of the village financial system. The benefits of this research are expected to be considered for the village government in evaluating the utilization of the Village Finance System and the contribution in enriching the research in the Rural Finance Field.